Aplikasi Pengukuran Tingkat Stres Pada Mahasiswa Tingkat Akhir Dengan Metode Certainty Factor - Sari, Yayang (Publica Scientific Solution, 2023)
Introduction: This stress level measurement application for final year students provides information about the level of stress experienced by students based on the symptoms felt by students, by displaying the results of the diagnosis in the form of the selected symptoms, the level of stress experienced along with the percentage of beliefs, and the solutions recommended. Purpose:to build a web-based expert system to measure stress levels in final year students and find out the level of stress experienced by students and provide recommendations for solutions to these students by applying the certainty factor method. Method: This study uses a quantitative method by carrying out a calculation process using the ceratinty factor, namely the calculation process is obtained from the quantitative value of the selected symptoms and then calculated based on the CF formula. Results: This application has an accuracy rate between the system and experts worth 90% based on 20 cases that have been tested, which shows that the certainty factor method can be applied in measuring stress levels in final year students. Conclusion: this application can be applied to measure stress levels in final year students with an accuracy value of 90%.